2016
DOI: 10.1080/10503307.2016.1177673
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: In-session silences are associated with client attachment insecurity, therapeutic alliance, and treatment outcome

Abstract: The study further validates the PICS. Findings indicate that therapists may be able to use in-session silences as an indicator of client attachment insecurity and as a prognostic sign of eventual treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 30 publications
2
42
2
Order By: Relevance
“…The current study findings might imply that patients, such as Mary, who present short and infrequent pauses and low jitter values may progress rapidly in forming an alliance with their therapist. Previous studies have shown an association between infrequent pauses and verbal fluency (Martins, Vieira, Loureiro, & Santos, 2007) and a tendency to engage and bond easily (Daniel, Folke, Lunn, Gondan, & Poulsen, 2018; Levitt, 2001). Also, Mary's low pretreatment jitter values reflect a steady, non‐trembling voice quality, which previous studies have associated with low distress and low anxiety levels (Juslin & Scherer, 2005).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The current study findings might imply that patients, such as Mary, who present short and infrequent pauses and low jitter values may progress rapidly in forming an alliance with their therapist. Previous studies have shown an association between infrequent pauses and verbal fluency (Martins, Vieira, Loureiro, & Santos, 2007) and a tendency to engage and bond easily (Daniel, Folke, Lunn, Gondan, & Poulsen, 2018; Levitt, 2001). Also, Mary's low pretreatment jitter values reflect a steady, non‐trembling voice quality, which previous studies have associated with low distress and low anxiety levels (Juslin & Scherer, 2005).…”
Section: Resultsmentioning
confidence: 97%
“…The current study findings might imply that patients, such as Aaron, who present pretreatment high levels of jitter and pauses may progress slowly in forming an alliance with their therapist. Moreover, previous studies have shown an association between high pause levels and a tendency to disengage from the therapy, a dynamic that can undermine alliance formation (Daniel, Folke, Lunn, Gondan, & Poulsen, 2018; Levitt, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoey, 2020). We applied the same 3-s minimum criterion as was applied in Levitt's research (1998Levitt's research ( , 2001 and also in the studies that used the PICS manual for their data analysis (Frankel et al, 2006;Stringer et al, 2010;Daniel et al, 2018). The rationale behind the minimum duration of 3 s is that these silences are considered meaningful and not just accidental disfluencies (Stringer et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to secure patients, dismissing patients detail narratives infrequently or their narratives are exceedingly terse (Daniel, 2011 ) they contain more pauses (Daniel, Folke, Lunn, Gondan, & Poulsen, 2018 ), and lack vividness (Talia et al, 2017). While these patients’ discourse is coherent and easy to follow, it may give the impression that the speaker is not interested in receiving support or validation from the therapist.…”
Section: Attachment and Communication In The Clinical Contextmentioning
confidence: 99%